SIMILARITIES AND DIFFERENCES OF MOOD IN ENGLISH AND UZBEK LANGUAGES - Kholmamatova Anora, Mukhamadiyev Aziz Shavkatovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
When expressing a speaker's attitude toward the activity or situation that the verb is indicating, mood—a grammatical category—is extremely important. It's an essential component of many languages, like Uzbek and English, and allows speakers to express a variety of nuances, including wishes, possibilities, orders, and assertions. Recognizing the ways in which these two languages employ mood differs and similarly offers important insights into their respective cultural settings and syntactic and semantic structures. The imperative, subjunctive, and indicative moods are the three main ones in English. Statements of facts and opinions belong in the indicative mood; orders and requests belong in the imperative mood; wishes, fictitious scenarios, and actions that are not true to reality belong in the subjunctive mood. Despite its limited usage, the subjunctive mood in English is still a crucial part of the language's grammatical structure. An extension of the Turkic language family, Uzbek similarly uses the indicative, imperative, and subjunctive moods, but it also has the optative and conditional moods. In contrast to the imperative mood, which gives directives, the indicative mood works similarly to its English counterpart. Nonetheless, Uzbek uses the subjunctive mood more frequently, frequently covering situations where English would use conditional structures. One of Uzbek's distinctive moods, optative, conveys wishes and desires, expanding the expressive possibilities of the language. We are better able to understand the similarities and distinctive qualities of each language when we compare these components of mood in Uzbek and English. This comparative analysis illuminates the linguistic diversity that influences human communication in addition to improving our comprehension of their grammatical systems.